The Baltics: banking crises observed - Fleming, Alexander; Chu, Lily L.; Bakker, Marie-Renée; World Bank. (Washington, DC : World Bank, Europe and Central Asia, Country Dept. IV, Enterprise and Financial Sector Development Division, 1996)
The Baltic Republics of Estonia, Latvia and Lithuania are in the vanguard of transition in the Former Soviet Union (FSU) and have made significant steps towards a market-based economy over the past five years
"September 1996"--Cover.
Includes bibliographical references (p. [34]-35).
osc 8/09/2021
Loans
Keywords: Banks and banking